The Effect of Corporate Social Responsibility (CSR) Disclosure on Stock Return Volatility in the Consumer Goods Sector on the Indonesia Stock Exchange - Ahmad Danda Aprindi; Fachruzzaman HI Hanafi (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the impact of Corporate Social Responsibility (CSR) disclosure on stock return volatility among consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative causal approach utilizing panel data is employed to examine the extent to which CSR disclosure influences stock return volatility. Stock return volatility is measured using two approaches: Idiosyncratic Volatility (IVOL), derived from a market model regression, and Realized Volatility, calculated via the standard deviation of daily returns. CSR disclosure is measured using the CSR Disclosure Index (CSRI) based on GRI Standards guidelines. The sample was selected using purposive sampling, and the estimation model was determined through a series of tests (Chow, Hausman, and Breusch–Pagan LM). The study is grounded in three primary theoretical frameworks: Signaling Theory, Stakeholder Theory, and Legitimacy Theory. It aims to address research gaps regarding the consumer goods sector on the IDX—where findings have remained inconsistent—while providing up-to-date empirical evidence from the 2020–2024 period.